Soluble CD137 Ameliorates Acute Type 1 Diabetes by Inducing T Cell Anergy - Itoh, Arata; Ortiz, Lorenzo; Kachapati, Kritika; Wu, Yuehong; Adams, David; Bednar, Kyle; Mukherjee, Shibabrata; Chougnet, Claire; Mittler, Robert S.; Chen, Yi-Guang; Dolan, Laurence; Ridgway, William M. (Frontiers in Immunology, 2019)
We show here that soluble CD137 (sCD137), the alternately spliced gene product of Tnfsfr9, effectively treats acute type 1 diabetes (T1D) in Nonobese diabetic (NOD) mice. sCD137 significantly delayed development of endstage disease, preserved insulin+ islet beta cells, and prevented progression to endstage T1D in some mice. We demonstrate that sCD137 induces CD4+ T cell anergy, suppressing antigen specific T cell proliferation and IL-2/IFN- secretion. Exogenous IL-2 reversed the sCD137 anergy effect. sCD137 greatly reduces inflammatory cytokine production by CD8 effector memory T cells, critical mediators of beta cell damage. We demonstrate that human T1D patients have decreased serum sCD137 compared to age matched controls (as do NOD mice compared to NOD congenic mice expressing a protective Tnfsfr9 allele), that human sCD137 is secreted by Tregs (as in mice), and that human soluble CD137 induces T cell suppression in human T cells. These findings provide a rationale for further investigation of sCD137 as a treatment for T1D and other T-cell mediated autoimmune diseases.